PENGARUH WAKTU MASERASI TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BUAH JERUK LEMON (Citrus limon Linn) - Asendy, Dyta Aprida; Widarta, I Wayan Rai; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 3 (2018): Jurnal ITEPA, 2018)
This research aimed to find effect of maceration time on antioxidant activity of lemon peel extract and to knew the best maceration time with highest antioxidant activity of lemon peel extract. This study used a Randomized Completly Design with treatment of maceration time of 6 levels: 18 hours, 24 hours, 30 hours, 36 hours, 42 hours and 48 hours. The experiment was repeated in three replication, so that 18 experimental units were obtained. The data were analyzed by ANOVA and then continued with DMRT. The results showed that the treatment of maceration time had significant effect on extraction yield, vitamin C, total phenol, total flavonoids and antioxidant activity of lemon peel extract. The best treatment was 36 hours with extraction yield was 26.96%, vitamin C was 5.22 mg AA/g, total flavonoids was 69.64 mg QE/g, total phenol was 16.73 mg GAE /g and antioxidant activity was 94.08%.